All Eyes on You: Debutantes' Explorations of Chinese Australian Womanhood at the Dragon Festival Ball. Issue 4 (2nd October 2021) - Gassin, Grace
Abstract : The Dragon Festival Ball, first held at the glamorous Trocadero Palais de Danse in 1938, remains one of the best-remembered historical events associated with Sydney's Chinese community. Effectively a tradition-within-a-tradition, the ball's debutante ritual, which began in 1941, has contributed greatly to the public memory of the ball, with striking images of the debutantes sustaining the Dragon Ball's inclusion in smartphone walking tours, exhibitions and more. To date, however, neither the women who made their debut at the Dragon Ball, nor the hopes and dreams which compelled them to take part, have been accorded scholarly attention matching their prominence in historical representations of Sydney's Chinese community. In this article, I focus on the memories of selected former debutantes and argue that recognising the complex meanings which these women attached to their debuts as young Chinese 'girls' living in White Australia is vital to understanding the Dragon Ball's multi-layered historical significances.